BALANCING INNOVATION AND MENTAL HEALTH: AI’S PSYCHOLOGICAL EFFECTS ON ENGLISH EDUCATION STAKEHOLDERS - Aly, Abdul Hamid; Rafli, Zainal; Muliastuti, Liliana (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
This investigation delves into the incorporation of Artificial Intelligence (AI) within the domain of English Language Teaching (ELT), underscoring its transformative capacity and the psychological ramifications for both educators and learners. AI instruments, such as adaptive learning platforms and chatbots, have fundamentally altered the landscape of language education by personalizing instructional experiences, automating monotonous tasks, and providing immediate feedback. These advancements significantly enhance motivation and engagement by cultivating a sense of achievement and competence among learners. Nonetheless, obstacles such as technostress, performance anxiety, and excessive dependency on AI instruments highlight the necessity for judicious integration. Educators express apprehensions regarding professional obsolescence, while learners face potential declines in self-efficacy and preparedness for autonomous tasks. This inquiry employs a systematic literature review (SLR) methodology, scrutinizing approximately 50 peer-reviewed articles to discern pivotal patterns, deficiencies, and trends. The results accentuate the criticality of reconciling technological advancement with humanistic principles. AI ought to augment human interaction, promoting collaboration, empathy, and social learning. Professional advancement for educators and culturally attuned implementations for diverse educational settings are essential to guarantee inclusive and efficacious AI integration. By addressing these dimensions, AI can facilitate equitable, engaging, and human-centered learning environments, thereby enhancing both pedagogical outcomes and psychological well-being. Subsequent research should investigate the comprehensive interplay between AI technologies and the psychological factors influencing their impact in educational contexts.